Implementasi Pembelajaran Bahasa Arab Materi Qawāʿid Menggunakan Media Visual Wall Chart di Madrasah Aliyah - Luthfiyah Khoirun Nisa; Abdul Mutholib (Universitas Islam Negeri Walisongo Semarang - Indonesia, 2024)
This study evaluates Arabic grammar (qawāʿid) instruction using visual wall charts in class XD at MA NU 03 Sunan Katong, Kaliwungu, Kendal, during the 2023/2024 academic year, assessing alignment with the SECTIONS framework. Employing a qualitative descriptive approach, the study involved the Arabic teacher, principal, and 33 students, with data collected via observations, interviews, documentation, and assessment records, analyzed using triangulation. Findings reveal that instruction comprises preparation (material development, wall chart creation), implementation (introducing concepts, examples, question-and-answer sessions, interactive exercises, discussions), and follow-up (group assessments, daily quizzes). The wall chart improved student outcomes, with an average score of 81 (meeting ≥75 criteria), notably for 70% of students without Arabic knowledge, and enhanced engagement among 60.6% visual learners. Per the SECTIONS framework, the wall chart aligns with seven criteria (Students, Ease of Use, Cost, Teaching and Media Selection, Interaction, Organizational Issues, Security and Privacy). However, it lacks Networking alignment due to its non-digital nature. Wall charts are effective for qawāʿid in resource-limited settings, though digital integration could enhance learning resources. Future research should explore multimodal approaches to accommodate diverse learning styles.